2022
DOI: 10.3390/foods11152317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Yeast Strains on Biogenic Amines, Volatile Compounds and Sensory Profile of Beer

Abstract: Nowadays, there are many sorts of beer, however, some of them, despite the good sensory and other quality indicators, could contain high concentrations of undesirable compounds, such biogenic amines (BA). The yeast strain (YS), used for fermentation, can cause desirable as well as undesirable changes in beer. The aim of this study was to evaluate the contribution of different YS (A-Saccharomyces cerevisiae var. diastaticus, B-Saccharomyces cerevisiae var. bayanus, C-Brettanomyces claussenii) on the main qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(76 reference statements)
2
2
0
Order By: Relevance
“…Overall, our results, based on the quantification of volatile compounds, showed that the yeast strain has a statistically significant impact on the majority of target volatile compounds. This result is in line with previous research showing that the yeast strain is a significant factor in the formation of main volatile compounds in beer and starter selection is a key factor to modulate beer characteristics ( De Simone et al, 2021 ; Matukas et al, 2022 ). A clustergram, which consists of a heatmap of standardized compound concentrations and dendrograms, was utilized as a tool for exploratory multivariate analysis of the volatile profiles of beers.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, our results, based on the quantification of volatile compounds, showed that the yeast strain has a statistically significant impact on the majority of target volatile compounds. This result is in line with previous research showing that the yeast strain is a significant factor in the formation of main volatile compounds in beer and starter selection is a key factor to modulate beer characteristics ( De Simone et al, 2021 ; Matukas et al, 2022 ). A clustergram, which consists of a heatmap of standardized compound concentrations and dendrograms, was utilized as a tool for exploratory multivariate analysis of the volatile profiles of beers.…”
Section: Resultssupporting
confidence: 93%
“…By considering that the variety and quantity of hop were kept constant among all beer samples, the difference in beer IBU might be correlated to the different capacity of yeast strain used for fermentation to preserve the α-acids from hop. These results enhance the role of starter on beer bitterness, conversely to data reported in other studies in which no differences in IBU were found among beers fermented with different starters ( Matukas et al, 2022 ). Beer color, a commercial parameter crucial for quality product, is affected by amount and quality of the used malt; it usually can range from pale (0–15 EBC), amber (15–35 EBC), and dark (35–80 EBC).…”
Section: Resultssupporting
confidence: 85%
“…That is a result comparable to those obtained by Corbu et al, 2023, and Fernández-Pacheco et al, 2021 [ 59 , 60 ]. However, the strains 27_Sacch_cerevisiae, 32_Pich_kluyveri and 34_Metsch_pulcherrima showed the ability to produce biogenic amines (BAs) that excludes them as candidates for potentially probiotic strains [ 43 ], despite their promising properties in previous assays, due to potential risks for consumers [ 61 , 62 ]. Both Caruso et al, 2001, and Delgado-Ospina et al, 2021, showed that strains belonging to M. pulcherrima , S. cerevisiae and P. kluyveri might produce BAs [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of fermented beverages depends largely on the type of yeast strain used in their production, the alcohol concentration and the extract, as well as aroma compounds [49]. Therefore, appropriate modification of the mashing profile or the use of specific yeast strains in the fermentative production of non-alcoholic beers may help preserve the metabolites responsible for their sensory profile [50].…”
Section: Content Of Odour-active Compounds In Low-alcohol Beers Produ...mentioning
confidence: 99%